The Effect of Work Discipline, Performance Allowance and Education Level on the Work Productivity of Employees of the Central Statistics Agency (BPS) of Langkat Regency - Syafrizal Elfi Sandri; Abdi Setiawan; Firman Ario (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze Work Discipline, Performance Allowances and Education Levels on Employee Work Productivity at the Central Statistics Agency (BPS) of Langkat Regency. Where there are Bound Variables, namely Work Productivity and there are three independent variables, namely Work Discipline, Performance Allowance and Education Level. This study uses primary data by searching for data through the Office of the Central Statistics Agency (BPS) of Lalat Regency. The data analysis model in this study uses multiple linear regression. The results of the study showed that the variables of work discipline, work allowance and education level had a significant effect on the work productivity of employees at the Central Statistics Agency (BPS) of Langkat Regency.